Antioxidant Effect of a Dihydropyridine Calcium Antagonist Nitrendipine in Streptozotocin-Induced Diabetes - Unuvar, S.; Gursoy, S.; Berk, A.; Kaymaz, B.; Ilhan, N.; Aktay, G. (Pleiades Publishing Ltd, 2020)
The present study aims to evaluate the effects of a dihydropyridine (DHP) derivative calcium channel antagonist nitrendipine (NIT) on lipid peroxidation (LPO), liver enzyme markers, glucose and lipid profile in rats with streptozotocin (STZ)-induced diabetes. A total of 24 female Sprague Dawley rats were classified into three groups as controls, STZ and STZ+NIT. Fasting blood glucose (FBG), triglyceride (TG), total cholesterol (TC) and high-density lipoprotein (HDL) levels, and alanine aminotransferase (ALT) and aspartate aminotransferase (AST) activity were measured seven weeks after the administration of STZ and NIT. The levels of thiobarbituric acid substance (TBARS), glutathione (GSH) and total thiol content (T-SH), as well as the levels of nitric oxide and metabolites (NO, nitrate, nitrite), were evaluated to assess the level of lipid peroxidation in liver, brain, kidney, heart and eye tissues. STZ significantly increased FBG levels, ALT and AST activity, and TBARS levels (p < 0.001, for all), and significantly reduced the levels of GSH and T-SH (p < 0.05), as well as total NO and nitrate (p < 0.001). STZ triggered LPO in tissues, while simultaneously causing a marked decrease in endogenous antioxidant content. NIT administration protect the kidney (p < 0.05), heart (p < 0.01), brain (p < 0.001) and eye (p < 0.05) tissues from LPO, and also normalized the elevated FBG levels and the activity of ALT and AST (p < 0.001, for all). NIT further stimulated GSH and T-SH production, particularly in the liver, kidney and heart tissues. The results of the present study suggest that NIT shows hypoglycemic activity in STZ-DM rats by increasing insulin sensitivity in the peripheral target tissues.
Keywords: diabetes mellitus; nitrendipine; liver enzymes; oxidative stress; streptozotocin